Passivity-based event-triggered control for a class of switched nonlinear systems. (June 2022) - Cao, Zhengbao; Zhao, Jun
Abstract: A static output feedback based event-triggered control mechanism for a class of switched nonlinear systems with a passivity property is proposed in this paper. Each subsystem of such a switched system does not necessarily have passivity in the classical sense, while maintaining the passivity property only on the active time intervals. Moreover, passivity is based on multiple storage functions and the storage functions are allowed to increase at switching instants. The proposed event-triggered output feedback controller can not only maintain asymptotic stability but also exclude Zeno behavior under some conditions. Finally, a numerical example is presented to illustrate the effectiveness of the method. Highlights: We consider the asymptotic stability problem for switched nonlinear systems with passivity via event-triggered control, which is the first time to investigate. We remove the assumptions required in the existing results to exclude Zeno behavior. The event-triggered control can not only guarantee asymptotic stability without Zeno behavior but also have the property that for any two adjacent triggering instants, if the later is not a switching instants, then the positive lower bound of inter-execution times can be obtained.